Management of Molar Pregnancy During COVID-19 Pandemic - Parsa, Yekta; Shokri, Nazila; Keshavarz, Pedram; Moridi, Atefeh (Novelty in Biomedicine, 2022)
Molar pregnancy is a group of diseases called gestational trophoblastic disease (GTD) that originates in the placenta and has the potential to invade the uterus and metastasize locally1, 2. During the past months, the novel coronavirus disease 2019 (COVID-19) has been responsible for the worldwide pandemic3. Patients usually go to the hospital only if they need high emergency aid or have a high-risk condition in this quarantine situation. Hence, this situation can impact diagnosing and managing benign and malignant molar pregnancy, and the diagnosis might be delayed.